Evaluation of Musculoskeletal Disorders in Household Appliances Manufacturing Company - Aioob Ghanbary; Ehsan Habibi; Arezou Abbaspour Darbandy (Iranian Journal of Health, Safety and Environment, 2015)
Work-related musculoskeletal disorders are the most prevalent work-related disorders and injuries and being the main cause of disability. This study was conducted to assessment of the prevalence of musculoskeletal disorders in worker company household appliances production. Posture analysis was evaluated by OWAS method and prevalence of musculoskeletal disorders by Nordic questionnaire. With evaluating musculoskeletal disorders among company household appliances production can intervention action to reduce musculoskeletal disorders was carried out. This cross-sectional study was performed on 100 workers of the appliance manufacturing industry. These Individuals were included 15 persons from foam injection workshop, 17 persons from molding workshop, 17 operators of presses, 17 persons from packaging, 17 person from cutting unit and 17 operators of rivet. The Nordic questionnaire was completed by Individuals for the organs of arm, back, leg and wrist and Posture analysis was performed by OWAS method. The data were analyzed using Spss software version 18 and descriptive statistics and Anova test. Nordic questionnaire results revealed that highest disorders were observed in the arm (25%), back (22%) and leg (21%). Also Anova test showed that was observed a significant correlation respectively between age and work experience with the prevalence of musculoskeletal disorders (p<0.02) (p<0.01). The results showed based on the level of risk OWAS for each job respectively, the highest level of risk associated with foam injection unit, packaging and cutting unit (risk level 4) and the lowest level of risk associated with molding workshop unit (risk level 2).The results of this study showed that household appliances Manufacturing workers due to the nature of their jobs are at risk of musculoskeletal disorders and Ergonomic interventions to do such as workstation redesign, reduced working hours, cycle of rest-work development.